Challenges faced by elderly patients with cancer in low-and-middle-income countries during the COVID-19 pandemic - Isaac Olufadewa; Miracle Adesina; Toluwase Ayorinde; Ruth Oladele; Funmilayo Abudu (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2021)
Studies have shown that elderly people with co-morbidities are at a higher risk of dying from the SARS-CoV-2 virus. The situation is worse for the 70% of the elderly population who reside in low-and-middle income countries (LMICs) with poor access to good healthcare systems. Elderly patients with cancer in LMICs face numerous barriers to accessing quality health information and services. These barriers have been further exacerbated by the ongoing COVID-19 pandemic. It is therefore necessary that solutions to these barriers are proffered and appropriate measures are put in place to mitigate these barriers. This article outlines not only some of the challenges faced by elderly patients with cancer living in LMICs in the wake of the COVID-19 pandemic, it also provides reliable and evidence-based solutions that would be useful to the government and other stakeholders in the health system. This would help to achieve a compassionate, comprehensive and inclusive healthcare for elderly cancer patients in the COVID-19 pandemic era.